Increased platelets count in HIV-1 uninfected infants born from HIV-1 infected mothers - Anicet Christel Maloupazoa Siawaya; Amandine Mveang-Nzoghe; Chérone Nancy Mbani Mpega; Marielle Leboueny; Ofilia Mvoundza Ndjindji; Armel Mintsa Ndong; Paulin N. Essone; Joel Fleury Djoba Siawaya (Hematology Reports, 2019)
HIV-exposed uninfected infants (HEU) represent a growing population in developing countries including Gabon. Several studies have shown the vulnerability of these infants toward infectious diseases. The aim of the study was to contribute to the global effort to understand how HIVexposure or anti retroviral therapy affects infants’ blood elements. We assessed HEU infants’ complete blood count using a blood analyzer instrument. Our investigations showed that among the observed clinically relevant hematological abnormalities events, thrombocytosis was the most prevalent clinically relevant hematological abnormality associated with HEU infants’. We showed that HEU infants had significantly higher platelets count than HUinfants. Therefore, higher level of platelets seems to characterize HEU infants when compared to HU infants.